Dewey defeats Truman a novel - Mallon, Thomas 1951- (Pantheon Books, 1997)
The story of a 1940s small town, its secrets, intrigues and romances. The setting is Owosso, Michigan, and the occasion is a federal election. The citizens of Owosso are concerned by the election because Owosso is the hometown of one of the candidates. By the author of Henry and Clara.
Keywords: Dewey, Thomas E <1902-1971> -- (Thomas Edmund) -- Fiction; Truman, Harry S. <1884-1972> -- Fiction; Presidents -- Election -- Fiction; Owosso (Mich.) -- Fiction; Biographical fiction; Love stories